ANALISIS KOMPARASI KINERJA KEUANGAN DESA DI KECAMATAN SIMPANG KATIS KABUPATEN BANGKA TENGAH - Dony Yanuar (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2015)
This study aims to analyze and determine financial performance comparisons between villages of Katis Simpang district of Central Bangka regency during period 2010-2012; as well as to analyze and determine the effectiveness of the allocation, management and use of the Village Budget (APBDes) at Simpang Katis District, Central Bangka regency during the same period. This research uses quantitative method. The sample is the local governmentof Simpang Katis district, Central Bangka regency. The analytical tools used to determine the financial performance comparison of the village are analisis of spending ratio, analysis of spending growth, analysis of expenditure balance, analysis of expenditure efficiency, and analysis of budget allocations in support of the mission of the Rural Development Plan (RPJMDes). The results shows that there are differences and similarities in terms of the management of direct spending, indirect spending, spending on personnel, expenditure growth, expenditure balance, expenditure efficiency, and budget allocations in supporting the mission of the Rural Medium-Term Development Plan (RPJMDes). In general the financial performance of Simpang Katis District, Central Bangka regency, is in the range of good to excellent.Keywords : Financial Performance of local government, APBDes, Financial ratios Analysis